Influence of some anthropometric and motor parameters on triple jump - Ramadani, L.; Rashiti, N.; Shkodra, M.; Heta, G. (Journal of Education, Health and Sport, 2021)
Athletics disciplines are characterized by motor movements that can be successfully applied during the educational process or through other forms of exercise, which significantly affect the development of general psychophysical abilities of individuals. Each of the disciplines of athletics acts on the development of individual abilities, but also on the general psychophysical status of man and for this reason athletics is called the "queen of sports". Athletic activities have a characteristic of participant inclusion.The values of the paper will be based on the purpose of anthropometric, basic motor and specific motor characteristics of students aged 21 years ± 6 months.A total of 70 male students, 7 anthropometric variables, 7 motor variables and 1 specific motor variable that were tested during the period of May, of the academic year, 2020/2021 were included in the research.In the basic parameters students, based on the results achieved in this anthropometric variable, are presented as a moderately homogeneous group.Although it is seen that the acquired flexibility and convexity (Skewness and Kurtosis) have a pronounced asymmetry, in the vast majority of anthropometric variables. Although it is seen that the acquired flexibility and convexity (Skewness and Kurtosis) have a pronounced asymmetry, in the vast majority of motor and criterion variables. Thus the statistically significant coefficients of the variables with the highest degree of statistical inference (p <0.01) are denoted by two asterisks. With easier statistical conclusion criterion (p <0.05) correlation coefficients. All variables have statistically significant correlation to all anthropometric, basic and criterion motor variables.